Catheter Ablation of Focal Atrial Tachycardia from the Aortic Cusp: The Role of Electroanatomic Mapping and Intracardiac Echocardiography. Issue 1 (7th December 2010) - MLČOCHOVÁ, HANKA; WICHTERLE, DAN; PEICHL, PETR; KAUTZNER, JOSEF
<x xml:space="preserve">Abstract</x> Catheter ablation of periatrioventricular (peri‐AV) nodal atrial tachycardias (AT) from the noncoronary aortic cusp (NCC) can be challenging due to the close proximity of the AV node In such cases, intracardiac echocardiography (ICE) together with three‐dimensional mapping system can be helpful in guiding the ablation catheter and in assessing the anatomic relationship of the aorta to the surrounding structures. We report two patients with AT originating near the AV node who underwent successful catheter ablation from the NCC. ICE proved useful in positioning the ablation catheter within the aortic cusps. Electroanatomic mapping enabled tagging the earliest activation site and renavigation back. (PACE 2013; 36:e19–e22)